2013
DOI: 10.1097/yco.0b013e328365a2e7
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the neurobiology of eating disorders

Abstract: New biological models are being developed which explain causal and maintaining factors. The RDoC construct may be used to systematize these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Many of the observed neurocognitive deficits implicated in EDs occur in the area of executive function (EF; Kanakam & Treasure, 2013; van Elburg & Treasure, 2013; Van den Eynde et al, 2011). EF is an umbrella term that refers to a set of neuropsychological processes (primarily centered in prefrontal regions) that govern higher-level, goal-directed behavior (Miyake et al, 2000).…”
Section: Neurocognitive Deficits In Eating Disordersmentioning
confidence: 99%
“…Many of the observed neurocognitive deficits implicated in EDs occur in the area of executive function (EF; Kanakam & Treasure, 2013; van Elburg & Treasure, 2013; Van den Eynde et al, 2011). EF is an umbrella term that refers to a set of neuropsychological processes (primarily centered in prefrontal regions) that govern higher-level, goal-directed behavior (Miyake et al, 2000).…”
Section: Neurocognitive Deficits In Eating Disordersmentioning
confidence: 99%
“…Anorexia nervosa (AN), bulimia nervosa (BN) and binge-eating disorder (BED) are the main forms of eating disorders (EDs) with a combined prevalence of up to 5% of women and 2% of men. 1 Although significant advances in understanding the neurobiological changes of ED have been achieved, 2 , 3 , 4 the molecular mechanisms triggering the onset and maintenance of ED still remain unknown, and the specific genetic influence is uncertain. 5 Accordingly, the unknown pathophysiology of ED explains the absence of specific pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The associated mental health concerns of obesity are well established as an indirect connection with using food as a reward; however, some research now cites the direct physiological changes to the brain and neurological reward systems in relation to eating behaviors . Especially for individuals with eating disorders, as well as those who meet the classification for obesity, the brain's food and reward neural circuitry is potentially altered in ways in which food becomes more rewarding . Researchers also have found that study participants with bulimia nervosa worked harder for food rewards as compared with controls without an eating disorder .…”
Section: Resultsmentioning
confidence: 99%